MEMAHAMI ANTROPOLOGI STRUKTURAL CLAUDE LEVI-STRAUSS - Gusti A. B Menoh (Universitas Kristen Satya Wacana, 2013)
French structuralism pioneered by Saussure. The term structure is always pointing to the understanding of language as a system. By the school of Prague (Jacobson and Trubetzkoy) term structure refers to the understanding of the structure of a system Saussurean structural linguistic methods would also schools of Prague is then influenced Levi-Strauss. Levi-Strauss develop the linguistic methods and apply them in social anthropology, so the approach is called structuralism ethnological or anthropological structural. In this approach, (1) Relation decisive difference. Culture is seen as grammar, and task analysis of the cultural phenomenon is no longer understand the symptoms of the particular separate / distinct, but found